Ladijske potniške evidence kot vir za zgodovino izseljenstva, s posebnim ozirom na izseljenske sezname tržaškega pristanišča - Kalc, Aleksej (Dve domovini, 1996)
After the introduction, dedicated to the characteristics and possibilities of using passenger records as a source for studying transoceanic emigration processes, the author presents ship emigration records produced by the port authorities of the Austrian national emigration port of Trieste during the years 1912-1914. They include the historical overview and a critical discussion of the source and the content, especially from the perspective of structural and other research on Slovene emigration processes, which are limited by the lack and/or inadequacy of official statistics.
Keywords: 1912-1914; primary source; pristanišča; slovenski izseljenci; Trst; zgodovinski pregledi; zgodovinski viri